2013
DOI: 10.1080/09593330.2013.841267
|View full text |Cite
|
Sign up to set email alerts
|

Competitive effects on mercury removal by an agricultural waste: application to synthetic and natural spiked waters

Abstract: In this work, the efficiency of a local and highly, available agricultural waste, the raw rice husk, was used to remove mercury (Hg) from synthetic and natural waters, spiked with concentrations that reflect the contamination problems found in the environment. Different operating conditions were tested, including initial pH, ionic strength, the presence of co-ions (cadmium) and organic matter. The sorption efficiency of rice husk was slightly affected by the presence H+ ions (pH range between 3 and 9), but in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…River water is a complex matrix comprising of various ions which can compete for available binding sites on the sorbent. Moreover, the presence of organic matters in this natural system restricts the mobility of mercuric ions and complicates the adsorption of Hg­(II) onto the sorbent. , Nevertheless, the experimental results revealed that the adsorption efficiency of Cyst-prGO was only slightly affected under this complex natural aquatic system. In spite of the lower specific surface area of Cyst-prGO (672 ± 1.0 m 2 g –1 ) compared to GO­(900 ± 1.0 m 2 g –1 ), a great removal efficiency of 91% was achieved in relation to GO (18%) in this real application study.…”
Section: Resultsmentioning
confidence: 94%
“…River water is a complex matrix comprising of various ions which can compete for available binding sites on the sorbent. Moreover, the presence of organic matters in this natural system restricts the mobility of mercuric ions and complicates the adsorption of Hg­(II) onto the sorbent. , Nevertheless, the experimental results revealed that the adsorption efficiency of Cyst-prGO was only slightly affected under this complex natural aquatic system. In spite of the lower specific surface area of Cyst-prGO (672 ± 1.0 m 2 g –1 ) compared to GO­(900 ± 1.0 m 2 g –1 ), a great removal efficiency of 91% was achieved in relation to GO (18%) in this real application study.…”
Section: Resultsmentioning
confidence: 94%
“…pesticides. [40] Bonding makes the toxics soluble in complex form and thus difficult to remove by conventional water treatment methods. [41] Waste streams, such as landfill leachates, or natural surface waters containing sufficient quantities of HS, may be of great interest for the production of clean non-fossil fuel, hydrogen, with HS serving as a sacrificial electron donor in photocatalytic water splitting: non-biodegradable waste decomposition and fuel production by a cost-efficient method are achieved simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…At low pH, the competition between increasing Na + concentrations and the fraction of Hg 2+ / HgOH + species that interacts through outer-sphere complexes for the sites of the RM surface and the enhanced electrical double layer surrounding the adsorbent particles acting as a shield that hinders the access of Hg 2+ to the surfaces could be responsible of this behaviour (Ghodbane and Hamdaoui 2006;Rocha et al 2014). Also, the observed sorption behaviour points to an increase of the net surface positive charge of RM at higher ionic strengths of NaNO 3 electrolyte at pH< pH pzc , as in the case of simple Fe oxides (Dzombak and Morel 1990;Stumm and Morgan 1996) or as also described for RM titrated in CsCl solutions (Atun and Hisarli 2000).…”
Section: Interacting Effect Of Electrolyte Concentration and Phmentioning
confidence: 99%